2016
DOI: 10.14503/thij-15-5025
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Abdominal Aortic Aneurysm Repair by Means of the Chimney Technique in a Patient with Crossed Fused Renal Ectopia

Abstract: Case ReportAn 88-year-old man with an expanding, asymptomatic infrarenal AAA was referred to our institution. A computed tomogram (CT) showed a 5-cm maximal diameter of the AAA (Fig. 1). The AAA had a 25-mm-long infrarenal neck that was 23 mm in diameter proximally and 25 mm distally. The patient had a crossed-over ectopic right kidney fused with the left kidney; the ectopic RA arose directly from the AAA and was 5.3 mm in diameter. The distal aortic neck was 25 mm in diameter, and the diameters of the common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the literature, there are case reports showing the technical aspects of the endovascular treatment of abdominal aortic aneurysm in patients with renal ectopia [14,15,16]. Tsuboi et al [17] reported a case of partial nephrectomy in patients with left-to-right crossed fused renal ectopia with clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are case reports showing the technical aspects of the endovascular treatment of abdominal aortic aneurysm in patients with renal ectopia [14,15,16]. Tsuboi et al [17] reported a case of partial nephrectomy in patients with left-to-right crossed fused renal ectopia with clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Kfoury et al . [ 9 ] and Colacchio et al . [ 10 ] placed self-expanding endografts (Viabahn Endoprosthesis, LG GORE, Delaware, USA) into RAs that arose from the AAA sacs in their cases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a parallel stent graft technique has been described to perfuse an ectopic renal artery originating from the AAA in a patient with a crossover ectopic right kidney fused with the left kidney. 30 A Viabahn–Gore (W. L. Gore) endograft reinforced with balloon-expandable stents was deployed in a parallel fashion with an Endurant II–Medtronic endograft iliac limb.…”
Section: Discussionmentioning
confidence: 99%